Self-assembly, stability, and photoresponse of PbS quantum dot films capped with mixed halide perovskite ligands. (March 2022) - Aynehband, Samaneh; Mohammadi, Maryam; Poushimin, Rana; Azar, Mahdi Hasanzadeh; Nunzi, Jean-Michel; Simchi, Abdolreza
Highlights: Oleic acid-capped PbS nanocrystals were drop casted on graphene/Si/SiO2 substrates. OA-ligands were substituted by I − /Br − inorganic-organic perovskite ligands. TEM shows nanocrystal fusion with the FAPbI3 perovskite. Substitution of I − by Br − ions results in more homogeneous and less defectuous layers. Photoresponse and solar stability of p -channel graphene-based transistors are improved with Br-rich ligands. Abstract: The type of passivating ligands and the ligand exchange method influence the quality of lead sulfide quantum dot films. This imparts on the efficiency of optoelectronic devices. To get a compact arrangement of the nanocrystals in a thin film (⁓100 nm) via self-assembling, we used organic-inorganic perovskites with mixed halides for the solid-state exchange of oleic acid ligands on PbS QDs (⁓ 4 nm). Formamidinium lead halides FAPbIx Br3-x ( x = 3, 2, 1, 0) were used. X-ray spectroscopy shows that successful replacement of oleic acid with FA happens by short immersion of the films (2 min) in the solution. Transmission electron microscopy shows that nano-scale cracks, short-range ordering, and fusion of the nanocrystals happen during the exchange with FAPbI3 . Gradual substitution of I − with Br − ions improves the film homogeneity with fewer defects (nano-scale holes and cracks). Uniform cubic assembly of the nanocrystals without defects and high coverage density is obtained with FAPbBr3 . The findings are applied to the fabrication of field effect phototransistors on Si/SiO2 /graphene wafers. Photoresponse of the devices indicates that the stability of the films in humidified air (26 °C and 51% humidity) is improved from less than 14 days for iodine to more than 60 days for bromine. The ILIGHT /IDARK ratio, responsivity, and specific detectivity increase by 64%, 55%, and 60%, respectively, with FAPbBr3 . Prevention of lead sulfide nanocrystal aggregation and the formation of large-scale self-assemblies with perovskite ligands is of technical importance for next-generation optoelectronic applications. Graphical abstract: Image, graphical abstract